Atypical fibrodysplasia ossificans progressiva diagnosed by whole‐exome sequencing. (21st April 2015) - Liu, Hao; Sawyer, Sarah L; Gos, Monika; Grynspan, David; Issa, Kheirie; Ramphal, Raveena; Rotaru, Carmen; Consortium, FORGE Canada; Majewski, Jacek; Boycott, Kym M; Graham, Gail; Bromwich, Matthew
Abstract : Fibrodysplasia ossificans progressiva (FOP) is a rare genetic disorder characterized by congenital malformations of the great toes and progressive heterotopic ossification of connective tissue that begins during the first decade of life. Our patient presented with intrauterine growth retardation, respiratory distress, neonatal onset soft tissue masses, bilateral hallux valgus, and congenital anomalies of the thyroid and uterus. She was initially diagnosed with atypical infantile myofibromatosis based on clinical and pathological findings. She underwent whole‐exome sequencing (WES) as part of the FORGE study to identify the gene for infantile myofibromatosis; however a de novo dominant mutation in ACVR1 (NM_001105.4:c.617G>A) revised the diagnosis to FOP. This patient highlights the utility of WES as an early diagnostic tool in the investigation of patients with unusual presentations of rare diseases, thereby providing clinicians with accurate molecular diagnoses and the opportunity to tailor clinical management to improve patient care. © 2015 Wiley Periodicals, Inc.